2003
DOI: 10.1128/jvi.77.7.4205-4220.2003
|View full text |Cite
|
Sign up to set email alerts
|

Global Changes in Kaposi's Sarcoma-Associated Virus Gene Expression Patterns following Expression of a Tetracycline-Inducible Rta Transactivator

Abstract: An important step in the herpesvirus life cycle is the switch from latency to lytic reactivation. In order to study the life cycle of Kaposi's sarcoma-associated herpesvirus (KSHV), we developed a gene expression system in KSHV-infected primary effusion lymphoma cells. This system uses Flp-mediated efficient recombination and tetracycline-inducible expression. The Rta transcriptional activator, which acts as a molecular switch for lytic reactivation of KSHV, was efficiently integrated downstream of the Flp rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
343
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(359 citation statements)
references
References 101 publications
15
343
1
Order By: Relevance
“…Because the mode of action of the inducers (e.g., phorbol ester or butyrate) is complex and the fraction of cells affected is relatively small, we chose to measure the expression kinetics of vPK by K-Rta-mediated reactivation. In the TREx-K-Rta BCBL-1 cell line (36), a derivative of the BCBL cell line, the expression of K-Rta is induced by DOX, resulting in a well-ordered KSHV gene expression program and a relatively synchronized cycle of viral replication in nearly all cells (19,36). RNA from induced cells was analyzed by Northern blot analysis, which showed that vPK is encoded in two transcripts (4.2 and 3.6 kb), together with ORF37 and ORF38.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the mode of action of the inducers (e.g., phorbol ester or butyrate) is complex and the fraction of cells affected is relatively small, we chose to measure the expression kinetics of vPK by K-Rta-mediated reactivation. In the TREx-K-Rta BCBL-1 cell line (36), a derivative of the BCBL cell line, the expression of K-Rta is induced by DOX, resulting in a well-ordered KSHV gene expression program and a relatively synchronized cycle of viral replication in nearly all cells (19,36). RNA from induced cells was analyzed by Northern blot analysis, which showed that vPK is encoded in two transcripts (4.2 and 3.6 kb), together with ORF37 and ORF38.…”
Section: Resultsmentioning
confidence: 99%
“…Human embryonic kidney epithelial 293 cells and 293T cells were grown in monolayer culture in Dulbecco's modified Eagle medium supplemented with 10% fetal bovine serum (FBS) in the presence of 5% CO 2 . The TREx-KRta BCBL-1 cell line, generated by Nakamura et al (36), was cultured in RPMI 1640 medium supplemented with 15% FBS, 100 g/ml of blasticidin (Invitrogen), and 100 g/ml of hygromycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…To induce ORF57 expression and virus lytic replication, KSHV-infected cells were treated with 0.6 mM valproate (VA), 0.3 mM butyrate, or 20 ng/ml of 12-O-tetradecanoylphorbol-13-acetate. Doxycycline (dox)-inducible TREx BCBL-1 RTA and vector control cell lines were cultured as described (14).…”
Section: Methodsmentioning
confidence: 99%
“…1B). To exclude the possible nonspecific effects of chemical inducers, this observation was further verified in TREx BCBL-1 RTA cells (14), which inducibly express RTA (ORF50), a potent transactivator for KSHV lytic induction (24). RTA induction by dox in these cells led to the production of both full-length and cleaved ORF57, along with the production of cleaved PARP (Fig.…”
Section: Induction Of Kshv Lytic Infection In Kshvmentioning
confidence: 99%
“…Also expressed during latency are transcripts derived from the K12 gene of KSHV [103], although expression of this gene is markedly up-regulated during the early stages of the lytic cycle, leading to its classification as a 'latent-lytic' [104] or even 'late' [105,106] gene. One of these transcripts encodes a protein, 'kaposin A', which has been reported to have transforming activity in rodent fibroblasts [107] and induces lymphocyte aggregation and adhesion possibly mediated through its direct interaction with cytohesin-1, a guanine nucleotide exchange factor for ARF GTPases and regulator of integrin-mediated cell adhesion [108,109].…”
Section: Kshv Latency and Latent Viral Genes In Ksmentioning
confidence: 99%